Near-surface air temperatures at site MB_Site1Exposed132 from the southern aspect of Mount Baker, USA - Town, Michael S; Wang, Felicity; Mehring, Chip; Parry, Devin; Searl, Logan; Dron-Smith, Gen; Block, Greta; Albrecht, Alexander; Anand, Tanvi; Bashore, Colman; Borowski, Mila; Bowen, Elizabeth; et al. (In: Town, MS et al. (2025): Distributed near-surface air and soil temperatures from the southern aspect of Mount Baker, USA from 2018-2024 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984453, 2025)
We present temperature measurements from the Mount Baker Climate Laboratory (MBCL; https://esr-mbcl.github.io/MBCL/). The MBCL is a citizen science effort that has operated continuously since July 2018 on the southern aspect of‬ ‭Mount Baker, Washington, USA. Here we share data from July 2018 - July 2024. The measurements were made in strategic arrays at nine sites ranging from elevations of 1000 m to the summit (3287 m). Data were collected using autonomous temperature sensors (iButtons) deployed in waterproof graphite housings. Data were collected at 4.25 hourly intervals. At each possible site, temperature measurements of shallow soil and near-surface air temperature (shaded and unshaded) were made in arrays after Lundquist and Lott (2008) and Lundquist and Huggett (2008). Above the treeline, only soil temperatures were made. Data from eight of nine sites have been successfully retrieved over this time period. The sensor distribution across the southern aspect of Mount Baker was designed to coincide with a common, relatively safe ascent route to facilitate citizen science field logistics. The sensor array design and site distribution are intended to allow investigation into ‬monitoring of hydrological and atmospheric phenomena like snow extent, snow depth (at one site), snow year length, critical temperature thresholds, mountain lapse rates, and model or reanalysis intercomparisons. More uses are possible.‬
Keywords: air temperature; Cascades; Citizen science; mountain; Pacific Northwest; snow temperature; soil temperature